Cognition, Language and Aging 2016
DOI: 10.1075/z.200.05ded
|View full text |Cite
|
Sign up to set email alerts
|

Language comprehension in aging

Abstract: There is a lot of evidence that sentence comprehension ability declines in normally aging adults. This chapter reviews variables that contribute to age-related declines in comprehension. Older adults recognize words and parse sentences more slowly than younger adults, and make more comprehension errors. These changes in comprehension ability have been associated with age-related declines in general cognitive processes, such as working memory, and in perceptual abilities, such as hearing acuity. This chapter al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…In another study, DeCaro et al ( 2016 ) found that age did not significantly improve the prediction of comprehension accuracy when working memory capacity and hearing acuity were already present in the model. There are multiple candidate variables that may be related to successful language processing in older adults, including perceptual abilities which decline with age, such as hearing acuity (DeDe and Flax, 2016 ) and temporal processing abilities (Pichora-Fuller, 2003 ) in the case of spoken language. Other candidate mechanisms include cognitive abilities like processing speed (Salthouse, 1996 ), working memory (Payne et al, 2014 ; DeDe and Flax, 2016 ), inhibitory processes (Hasher and Zacks, 1988 ), and verbal fluency, which is thought to moderate the extent to which older adults use predictive processing (Federmeier et al, 2002 ; DeLong et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, DeCaro et al ( 2016 ) found that age did not significantly improve the prediction of comprehension accuracy when working memory capacity and hearing acuity were already present in the model. There are multiple candidate variables that may be related to successful language processing in older adults, including perceptual abilities which decline with age, such as hearing acuity (DeDe and Flax, 2016 ) and temporal processing abilities (Pichora-Fuller, 2003 ) in the case of spoken language. Other candidate mechanisms include cognitive abilities like processing speed (Salthouse, 1996 ), working memory (Payne et al, 2014 ; DeDe and Flax, 2016 ), inhibitory processes (Hasher and Zacks, 1988 ), and verbal fluency, which is thought to moderate the extent to which older adults use predictive processing (Federmeier et al, 2002 ; DeLong et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, we chose peripheral hearing loss as measured by hearing thresholds. Hearing loss is highly prevalent in older adults—approximately 20% at age 60 and 50% at age 70 (Goman and Lin, 2016 ; Bisgaard and Ruf, 2017 ; Mick et al, 2019 )—and hearing thresholds have been shown to influence many behavioral results in previous studies (Wingfield et al, 2006 ; DeCaro et al, 2016 ; DeDe and Flax, 2016 ), even in young adults (Ayasse et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these cognitive requirements, young adults usually understand well the information intended by a speaker. However, the older adults typically understand spoken narratives slower, make more errors, and remember less information (1)(2)(3), even though their basic linguistic functions (such as semantic and syntactic processing) are thought to be preserved (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these cognitive requirements, young adults can decipher the information intended by a speaker effortlessly. However, the older adults typically understand spoken narratives slower, make more errors, and remember less information (DeDe & Flax, 2016;Schneider et al, 2002;Zacks et al, 2006), even though their basic linguistic functions (such as semantic and syntactic processing) are thought to be preserved (Shafto & Tyler, 2014;Tyler et al, 2010).…”
Section: Introductionmentioning
confidence: 99%